Tackling suppressive cancer microenvironment by NARF-derived immune modulatory vaccine and its validation using simulation strategies - Paranthaman, Priyanga; Veerappapillai, Shanthi (Frontiers in Physics, 2024)
Targeting tumor microenvironment is beneficial and present an ideal setting for the development of futuristic immunotherapy. Here, we make use of Nuclear prelamin A recognition factor (NARF), a protein linked to the coactivation of transcriptional regulators in human breast cancer stem cells (CSC) in our investigation. The regions possess the ability to stimulate both T and B cells within the NARF protein were initially computed. These identified epitope areas were fused with an adjuvant such as RpfB and RpfE as well as linkers like AAY, GPGPG, KK, and EAAAK. The constructed vaccine was further characterized by assessing its physicochemical properties and population coverage. The potential interactions of the designed vaccine with different toll-like receptors were examined by a sequence of computational studies. Of note, docking study were employed to understand its mechanism of action. Molecular dynamics and immune simulation studies were conducted to comprehend more into their structural stability and immune responses. The resultant vaccine was backtranslated, codon-optimised and introduced into pET-28(+) vector. Altogether, we hypothesise that the designed NARF protein-based vaccine in our analysis could effectively provoke the immune responses in the target organism through TLR-7 binding and promotes MHC class-II mediated antigen presentation.